PENGARUH METODE FUN LEARNING PADA PEMAHAMAN SISWA TERHADAP SEJARAH KEBUDAYAAN ISLAM DI SEKOLAH ALAM INDONESIA CIBINONG - Ganjar; Hasan Basri; Lukman Mahdami (PT. IHLAS (Ilmu Adalah Segalanya) - BICARA CENTRE, 2026)
Education has an important role in understanding and maintaining Islamic culture. This thesis explores the application of the fun learning method as an innovative approach to improving students' understanding of Islamic cultural history. This study involved elementary school students and was conducted at the research site. The research method used is a quantitative method that involves planning, implementation, observation, data, and reflection. Fun learning is integrated into the learning process of Islamic cultural history, using various media and activities that attract students' attention The results of the study showed a significant increase in student participation, active involvement, and understanding of Islamic cultural history concepts. Students showed a positive response to the fun learning approach, which included the use of educational games, visual presentations, and group discussions. The steps taken in this study were random sampling by determining the location of the study, namely Sekolah Alam Indonesia Cibinong. The population in this study were several facilitators (teachers) totaling 27 and the author took 20 teachers. By paying attention to rxy, which is -0.682 with r table data of 0.444 at a significance of 5% and 0.561 at a significance of 1%, which means that there is a moderate or sufficient relationship between variables X and Y. So that the alternative hypothesis (Ha) is approved or accepted. So from the results above, it can be concluded that mastery of the fun learning method affects the understanding of Islamic Cultural History of students at Sekolah Alam Indonesia Cibinong which has increased.